2001
DOI: 10.1074/jbc.m011590200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ca2+ in Insulin-stimulated Glucose Transport in 3T3-L1 Cells

Abstract: We have examined the requirement for Ca 2؉ in the signaling and trafficking pathways involved in insulinstimulated glucose uptake in 3T3-L1 adipocytes. Chelation of intracellular Ca 2؉ , using 1,2-bis (o-aminophenoxy)ethane-N,N,N,N-tetraacetic acid tetra (acetoxymethyl) ester (BAPTA-AM), resulted in >95% inhibition of insulin-stimulated glucose uptake. The calmodulin antagonist, W13, inhibited insulin-stimulated glucose uptake by 60%. Both BAPTA-AM and W13 inhibited Akt phosphorylation by 70 -75%. However, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
115
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 45 publications
17
115
3
Order By: Relevance
“…Similar mechanisms result in GLUT4 vesicle fusion in adipocytes and muscle cells. Whitehead et al (8) demonstrated, and we confirmed, that reduction of intracellular Ca 2ϩ ([Ca 2ϩ ] i ) using the membrane-permeable Ca 2ϩ -chelating agent BAPTA-AM diminished insulinstimulated glucose transport, whereas this reagent did not inhibit GLUT4 translocation to the plasma membrane (i.e., GLUT4 vesicle trafficking was not impaired) (8) (N.F., M.E., unpublished observation). These observations suggest that an appropriate intracellular Ca 2ϩ level may be required for the final docking/fusion steps of GLUT4 vesicles in adipocytes.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Similar mechanisms result in GLUT4 vesicle fusion in adipocytes and muscle cells. Whitehead et al (8) demonstrated, and we confirmed, that reduction of intracellular Ca 2ϩ ([Ca 2ϩ ] i ) using the membrane-permeable Ca 2ϩ -chelating agent BAPTA-AM diminished insulinstimulated glucose transport, whereas this reagent did not inhibit GLUT4 translocation to the plasma membrane (i.e., GLUT4 vesicle trafficking was not impaired) (8) (N.F., M.E., unpublished observation). These observations suggest that an appropriate intracellular Ca 2ϩ level may be required for the final docking/fusion steps of GLUT4 vesicles in adipocytes.…”
supporting
confidence: 54%
“…In 2001, Whitehead et al (8) first reported that a calcium chelator, BAPTA-AM, inhibited GLUT4 externalization and glucose uptake. However, the precise mechanism underlying calcium-dependent GLUT4 vesicle fusion remains unknown because no studies have as yet focused on Ca 2ϩ -sensing proteins in adipocytes.…”
Section: Doc2b Regulates Glut4 Vesicle Fusionmentioning
confidence: 99%
“…However, it is unclear whether impairment of the insulin signaling pathway is a decisive factor for determining defective glucose uptake and utilization. Insulin-stimulated glucose uptake was achieved by activating only 10-20% of insulin receptor substrate-1 (IRS-1) and Akt in one study (Whitehead et al, 2001), and insulinstimulated Akt activation was not severely impaired in obese individuals with insulin resistance in another study (Storgaard et al, 2004), indicating that factors other than an impaired insulin signaling pathway may be involved in the induction of insulin resistance. Additionally, a report that palmitate induces insulin resistance without a defect in insulin-stimulated Akt phosphorylation in the soleus muscle (Alkhateeb et al, 2007) suspects a role for impairment of the insulin signaling pathway in PIIR.…”
Section: Discussionmentioning
confidence: 99%
“…Because calcium and phosphoinositides are known to regulate insulinstimulated glucose transport (15)(16)(17)(18)(19), it would be interesting to test whether changes in Ca 2ϩ produced by insulin signaling affect the ability of E-Syt1 to bind phospholipids and how this might affect the interaction between E-Syt1 and GLUT4.…”
Section: Discussionmentioning
confidence: 99%